Effect of Training and Detraining in the Components of Physical Fitness in People Living With HIV/AIDS - Araujo, Juliany de Souza; Medeiros, Rafaela Catherine da Silva Cunha de; Silva, Tatiane Andreza Lima da; Medeiros, Danielle Coutinho de; Medeiros, Jason Azevedo de; Santos, Isis Kelly dos; Wilde, Phelipe; Cabral, Breno Guilherme de Araújo Tinoco; Medeiros, Radamés Maciel Vitor; Dantas, Paulo Moreira Silva (Frontiers in Physiology, 2021)
Abstract The aim of the study was to evaluate the effect of training and detraining on the physical fitness components of people living with HIV/AIDS (PLHA). The study was characterized as experimental with a sample composed of 21 people divided into 2 groups: 11 volunteers (PLHA, 46.9 ± 8.0 years, 63.8 ± 12.7 kg, 161.7 ± 8.7 cm, 7 men and 4 women), using antiretroviral therapy (ART) and 10 people without HIV/AIDS in the control group (CG, 43.8 ± 13.8 years, 75.2 ± 11.2 kg, 163.3 ± 7.8 cm, 3 men and 7 women), with the same average age and level of physical activity. The intervention, applied to both groups, consisted of combined training for 15 weeks, followed by detraining for 5 weeks. Before and after the training and detraining period the following parameters were evaluated: body composition by Dual Energy Radiological Absorptiometry (DXA), cardiorespiratory fitness by ergospirometer, and strength of upper and lower limbs by isometric dynamometer. The results show the effect of the intervention moments on the strength and oxygen consumption variables (time factor), considering the two study groups. Regarding the analysis of the interaction (group vs time), there was a significant effect on the isometric extension strength of the left (p = 0.019) and right (p = 0.030) knees, with training (left: 10.4%; right: 12.4%) and detraining (left: -10.8%; right: -12.1%) effect in PLHA, when compared with the control group (left: 8.1% and 3.9%, respectively; right: 11.5% and -0.2%, respectively). In addition, there was a significant interaction on ventilatory threshold 1 (p = 0.002), indicating a significantly greater increase with training (27.3%) and decrease with detraining (-22.7%) in the PLHA group compared with the Control group (19.9% and -6.7%, respectively). In conclusion, combined training and the subsequent period of detraining caused similar responses in body composition, isometric strength and cardiorespiratory fitness of PLHA and CG, except for the extensor strength of the lower limbs and ventilatory threshold 1, which presented positive effects on training and negative effects on detraining for PLHA.